Protective Role of α-Calcitonin Gene-Related Peptide in Cardiovascular Diseases - Kumar, Ambrish; Potts, Jay D.; DiPette, Donald J. (Frontiers in Physiology, 2019)
α-calcitonin gene related peptide (α-CGRP) is a regulatory neuropeptide of 37-amino acids. It is widely distributed in the central and peripheral nervous system, predominantly in cell bodies of the dorsal root ganglion (DRG). It is the most potent vasodilator known to date and has ionotropic and chronotropic effects. Using pharmacological and genetic approaches our laboratory and other research groups established the protective role of α-CGRP in various cardiovascular diseases such as heart failure, experimental hypertension, myocardial infarction, and myocardial ischemia/reperfusion injury (I/R injury). α-CGRP acts as a depressor to attenuate the rise in blood pressure in three different models of experimental hypertension: 1)- DOC- salt, 2)- Subtotal nephrectomy-salt, 3)- L-NAME induced hypertension during pregnancy. Subcutaneous administration of α-CGRP lowers the blood pressure in hypertensive and normotensive humans and rodents. Recent studies also demonstrated that an α-CGRP analogue, acylated α-CGRP, with extended half-life ( 7 h) reduces blood pressure in Ang-II induced hypertensive mouse, and protect against abdominal aortic constriction (AAC)-induced heart failure. Together, these studies suggest that α-CGRP, native or a modified form, may be a potential therapeutic agent to treat patients suffering from cardiac diseases.